Produksi Lipid Oleh Mikroalga Indigeneous Pada Media Air Gambut Dengan Penambahan Medium Basal Bold - Fauzani, Rhanti; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Peatlands are one type of wetland ecosystem. Indonesia's peat land area is about 14.95 million hectares spread across the island of Sumatra, Kalimantan. Microalgae are photosynthetic microorganisms capable of converting sunlight, water and carbon dioxide into biomass. In microalgae biomass contains beneficial essential ingredients, such as proteins, carbohydrates, lipids and nucleic acids. The microalgae used in this study were the Indigeneous microalgae from peat water. The purpose of this study is to determine the influence of the best variation in the addition of Basal Bold Medium (MBB) to the rate of cell growth and lipid production in the cultivation of microalgae indigeneous of peat water. The medium used for the cultivation of microalgae should be enriched with nutrients that include the nutrient elements of macronutrients (C, H, N, S, P, K, Mg and Ca) and micronutrient nutrients (Fe, Cu, Mn, Zn, Mo, V and Si). The results showed the best conditions gained in the addition of the medium of Basal Bold 1 ml/L, where the lipid content obtained is 29.44%, and the growth rate of cell/ML 825 x 104. Keywords: peat water, lipids, cellular growth rate, Basal Bold Medium